(untitled) (World Bulletin of Social Sciences, 2026)
The modernization of the education system has become one of the decisive conditions for the qualitative renewal of society and the sustainable development of the younger generation. In contemporary discourse, educational reform is no longer interpreted only as the renewal of infrastructure, technologies, or curricula. It is increasingly understood as a complex social process that shapes intellectual independence, moral responsibility, cultural identity, critical thinking, civic consciousness, and the ability of young people to correlate personal aspirations with the common good. From this standpoint, the spiritual development of youth should be examined not in a narrow confessional sense, but as the formation of an integral worldview grounded in values, ethical choice, social solidarity, respect for national culture, and openness to universal human ideals